As matemáticas no cotidiano de pessoas idosas da comunidade São José Operário, Belém-Pa: uma análise a partir da educação matemática crítica - MOREIRA, Elinalda da Silva (Universidade Federal do Pará, 2023)
This research aimed to analyze mathematics education, from a Critical perspective, in the daily lives of elderly people and as specific objectives: to describe mathematics in their daily lives and to identify mathematics throughout the lives of elderly people. The theorists who base this research are: Skovsmose, D’Ambrosio, Freire and others who contribute significantly to the construction of references. In order to produce the data, interviews were conducted with 6 elderly people, 4 women and 2 men. The locus of this study is the São José Operário community, located in the Bengui neighborhood, in Belém do Pará. The methodology is based on a qualitative approach, through case study, with semi-structured interview, focusing on Critical Mathematics Education, anchored in the studies of Skovsmose (2001, 2005, 2007, 2012, 2021). The results reveal that elderly people interact with mathematics in their daily and religious activities, they also bring “traumas” from the methodology used in the past to teach mathematics, since at the time, traditional teaching was used, based on the use of “palmations”. The categories reveal that because it is a rigid teaching, there was no continuation of studies, leading them to informal work, a reflection of a banking education evidenced by Freire, where the student was a being without opportunities for questioning and reflection in the classroom.